Health Care Reform and the Number of Doctor Visits - An Econometric Analysis - Rainer Winkelmann (Institute for the Study of Labor (IZA), 2001)
The paper evaluates the German health care reform of 1997, using the individual number of doctor visits as outcome measure. A new econometric model, the Probit-Poisson-log-normal model with correlated errors, describes the data better than existing count data models. Moreover, it has an attractive structural interpretation, as it allows the reforms to have a different effect at different parts of the distribution. The overall effect of the reform was a 10 percent reduction in the number of doctor visits. The effect was much larger in the lower part of the distribution than in the upper part.
Keywords: I18; C25; I11; 330; Co-payment; moral hazard; count data; probit-Poisson-log-normal model; Gesundheitsreform; Ärzte; Moral Hazard; Probit-Modell; Deutschland